Perbandingan Return on Asset, Return on Equity, Gross Profit Margin, Operating Profit Margin, dan Net Profit Margin Sebelum dan Semasa COVID-19 Pada PT Matahari Department Store, Tbk - Jefriyanto, Jefriyanto (Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine the impact of covid-19 on profitability at PT. Matahari Department Store, Tbk. Profitability is the ratio used to measure the level of profit obtained from sales and investment. Profitability concerns are Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM) and Net Profit Margin (NPM). The data is secondary data which includes financial reports for 2019 and 2020. The analysis tools is the profitability ratio and for analyzing the data, this study uses a descriptive method. The results of this study indicate that ROA, ROE, GPM, OPM and NPM have decreased between 2019 and 2020. This is because companies no longer have any profits in 2020. This decrease is due to the covid-19 outbreak which has caused national and international economies issues, including PT. Matahari Department Store, Tbk.